Cadmium resistance of endophytic bacteria and rizosféricas bacteria isolated from Oriza sativa in Colombia - Nataly Ayubb T; Armando Cerra G; Leonardo Chamorro A; Alexander Pérez C (Revista Colombiana de Ciencia Animal Recia, 2017)
The present study had as objective to evaluate in vitro the resistance of endophytic bacteria and rizospheric bacteria to different concentrations of Cadmium.This bacteria were isolated fron different tissues of commercial rice varieties and from bacteria isolated from the rhizosphere in rice plantations of the Nechí (Antioquía) and Achí (Bolivar).  Plant growth promotion was evaluated in vitro by nitrogen fixation, phosphate solubilization and siderophores production of endophytic bacteria. Of each tissue isolated from rice plants was carried out isolation in culture medium for endophytic bacteria, and the soil samples were serially diluted in peptone water. Each sample was determined the population density by counting in CFU / g of tissue and morphotypes were separated by shape, color, size and appearance in culture media. Significant differences were observed for density population of bacteria with respect to tissue, with higher values in root (4x1011 g/root), followed of the stem (3x1010g/etem), leaf (5x109 g/ leaf), flag leaf (3x109 g/ flag leaf) and with less density in panicle (4x108 g/panicle). The results of the identification with kit API were confirmed the presence of endophytic bacteria Burkholderia cepaceae and rizospheric bacteria Pseudomona fluorescens With the ability to tolerate different concentrations of Cd, fix nitrogen, solubilize phosphates and produce siderophores.